Evaluating the Quality of Wastewater Treated at the Step of Errachidia City (Morocco) - M., Ouhammi; M., Merzouki; H., Belhassan (Current Research on Geography, Earth Science and Environment Vol. 1, 2025)
Various sources of environmental pollution, especially in countries less aware of health risks, are caused by the growth of population, economy and urbanisation. Among these pollutants, wastewater is often discharged into the receiving environment without any treatment. The aim of this research is to analyse the physico-chemical and bacteriological properties of both raw and treated wastewater from the wastewater treatment plant (WWTP) in Errachidia, Morocco, throughout the year 2020, to assess the efficiency of the treatment process of the aerated lagoon system and to examine the potential for irrigation reuse. The average monthly data from January to December 2020 for the physico-chemical tests of treated wastewater are as follows: BOD5 = 94.45 mg O2/L; COD = 339.32 mg O2/L; SS = 87.67 mg/L. The findings indicate that these results meet the general discharge limit values for Moroccan surface waters, thereby contributing to environmental protection. Furthermore, the bacteriological findings reveal the presence of various microorganisms with average annual values where faecal coliforms (CF) are 680 CFU/100 ml; total coliforms (CT) are 2810 CFU/100 ml, and faecal streptococci are 46 UFC/100 ml, all of which are the recommended limit values set by Moroccan irrigation regulations (CF < 1000 CFU/100 ml), making them suitable for use in irrigation. It is recommended to adopt a tertiary treatment and disinfection to obtain treated water of acceptable microbiological quality for reuse in irrigation, allowing the protection of agricultural users and consumers of crops.